Management System Project for Textile Company using Risk Management Analysis - Lorio Purnomo; Chairani Putri Pratiwi; Rizka Astari Rahmatika; Rafki Chandra Wibawa; Siti Paramadita; Desman Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
As technology continues to advance across industries, the strategic role of information in organizations becomes increasingly evident. Recognizing the potential of information technology to enhance operational efficiency and customer satisfaction, various industries have integrated technology into their management systems. However, these innovations also introduce risks to the organization's information landscape. Risk management, therefore, emerges as a crucial discipline to identify, assess, and mitigate information technology-related risks. Textile companies, for instance, employ web-based management systems to support their operations, but encounter challenges hindering effective business process execution. This leads to reduced work performance and hampers goal attainment. This study aims to analyze the risks associated with web-based management systems in the textile industry and to suggest strategies for minimizing these risks. The research combines literature review and analytical methodologies to achieve its objectives. The literature review encompasses topics such as management systems, their components, and risk management. The research proposes a risk management process comprising nine stages: system characterization, identifying threats, determining vulnerabilities, analyzing controls, estimating probability, evaluating impact, assessing risk, proposing controls, and documenting results. Nevertheless, there is very little and/or scarce research on the use of technology throughout the textile industry. Thus, in order to fulfill the research emptiness within the use of information technology to increase the performance of the textile industry, this research underscores the critical role of risk management in safeguarding information technology systems within the textile industry.